TINGKAT KEEFEKTIVAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING PBLTERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA KELAS 5 SD - Duwiqi Darmawan, Awang; Arsyad Fardani, Much; Ermawati, Diana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
One of the low mathematical problem solving abilities of students is the lack of practice in solving non-routine problems. As many as 62% of class V students in filling out the questionnaire stated that when the teacher explained the material with lectures, this made the students' problem-solving abilities poor. The purpose of this research is 1) to analyze the effectiveness of the Problem Based Learning model on students' mathematical problem solving abilities. 2) to test the average mathematical problem solving ability of students using the Problem Based Learning learning model to achieve KKM 70 completeness. The results of the paired sample t test obtained a significance value (2-tailed) from this study of 0.001 (p < 0.05). So the results of the initial test (pretest) and final test (posttest) experienced significant (meaningful) changes. Based on the descriptive statistics of the initial test and final test, it is proven that the final test is higher, so H_0 is rejected and H_a is accepted. So, there is a significant average difference before and after implementing the Problem Based Learning learning model. Apart from that, based on the results of the one sample t test, P-Value = 0.026. Because the test carried out is a right-hand test, the P-Value=1/2× sig.(2-tailed)=1/2×0.026=0.013. this value is greater than 1/2∝=0.025. The P-Value is less than 0.025. So H_0 is rejected and H_a is accepted. So, the average mathematical problem solving ability of students using the Problem Based Learning model is more than 70.